Foreign Aid and Its Unintended Consequences - Koch, Dirk-Jan (Routledge, 2023)
Foreign aid and international development frequently bring with it a r ange of unintended consequences, both negative and positive. This book delves into these consequences, providing a fresh and comprehensive g uide to understanding and addressing them. The book starts by laying o ut a theoretical framework based on complexity thinking, before going on to explore the ten most prevalent kinds of unintended effects of fo reign aid: backlash effects, conflict effects, migration and resettlem ent effects, price effects, marginalization effects, behavioural effec ts, negative spillover effects, governance effects, environmental effe cts, and ripple effects. Each chapter revolves around a set of concret e case studies, analysing the mechanisms underpinning the unintended e ffects and proposing ways in which policymakers, practitioners, and ev aluators can tackle negative side effects and maximize positive side e ffects. The book also includes personal testimonies, a succinct overvi ew of unintended effects, and suggestions for further reading. Providi ng a clear overview of what side effects to anticipate when planning, executing, and evaluating aid, this book will be an important resource for students, development practitioners, and policymakers alike.